Investigation of a new acetogen isolated from an enrichment of the tammar wallaby forestomach - Gagen, Emma J.; Wang, Jiakun; Padmanabha, Jagadish; Liu, Jing; Carvalho de Carvalho, Isabela Pena [UNESP]; Liu, Jianxin; Webb, Richard I.; Al Jassim, Rafat; Morrison, Mark; Denman, Stuart E.; McSweeney, Christopher S. (Biomed Central Ltd, 2014)
Background: Forestomach fermentation in Australian marsupials such as wallabies and kangaroos, though analogous to rumen fermentation, results in lower methane emissions. Insights into hydrogenotrophy in these systems could help in devising strategies to reduce ruminal methanogenesis. Reductive acetogenesis may be a significant hydrogen sink in these systems and previous molecular analyses have revealed a novel diversity of putative acetogens in the tammar wallaby forestomach.Results: Methanogen-inhibited enrichment cultures prepared from tammar wallaby forestomach contents consumed hydrogen and produced primarily acetate. Functional gene (formyltetrahydrofolate synthetase and acetyl-CoA synthase) analyses revealed a restricted diversity of Clostridiales species as the putative acetogens in the cultures. A new acetogen (growth on H-2/CO2 with acetate as primary end product) designated isolate TWA4, was obtained from the cultures. Isolate TWA4 classified within the Lachnospiraceae and demonstrated > 97% rrs identity to previously isolated kangaroo acetogens. Isolate TWA4 was a potent hydrogenotroph and demonstrated excellent mixotrophic growth (concomitant consumption of hydrogen during heterotrophic growth) with glycerol. Mixotrophic growth of isolate TWA4 on glycerol resulted in increased cell densities and acetate production compared to autotrophic growth. Co-cultures with an autotrophic methanogen Methanobrevibacter smithii revealed that isolate TWA4 performed reductive acetogenesis under high hydrogen concentration (> 5 mM), but not at low concentrations. Under heterotrophic growth conditions, isolate TWA4 did not significantly stimulate methanogenesis in a co-culture with M. smithii contrary to the expectation for organisms growing fermentatively.Conclusions: The unique properties of tammar wallaby acetogens might be contributing factors to reduced methanogen numbers and methane emissions from tammar wallaby forestomach fermentation, compared to ruminal fermentation. The macropod forestomach may be a useful source of acetogens for future strategies to reduce methane emissions from ruminants, particularly if these strategies also include some level of methane suppression and/or acetogen stimulation, for example by harnessing mixotrophic growth capabilities
Keywords: Acetogen; Acetogenesis; Tammar wallaby; Rumen; Methanogenesis